2019
DOI: 10.1016/j.ijid.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Human encephalitis complicated with bilateral acute retinal necrosis associated with pseudorabies virus infection: A case report

Abstract: We report the case of a patient who presented with viral encephalitis and a pulmonary infection complicated with bilateral acute retinal necrosis after direct contact with diseased swine. Nextgeneration sequencing of the cerebrospinal fluid and vitreous humor detected pseudorabies virus (PRV) simultaneously. Intravenous acyclovir and dexamethasone treatment improved the symptoms of encephalitis, and vitrectomy surgery with silicone oil tamponade was used to treat the retinal detachment. This case implies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…PrV is the causative agent of Aujeszky's disease in pigs but infects a variety of mammals ranging from ruminants to carnivores, rodents and lagomorphs. Horses and primates resist infection [17], although evidence for rare human infections have been reported recently [18,19]. In adult pigs, the virus causes mostly respiratory illness, abortion or even subclinical infection, whereas piglets usually develop severe neurological signs.…”
Section: Introductionmentioning
confidence: 99%
“…PrV is the causative agent of Aujeszky's disease in pigs but infects a variety of mammals ranging from ruminants to carnivores, rodents and lagomorphs. Horses and primates resist infection [17], although evidence for rare human infections have been reported recently [18,19]. In adult pigs, the virus causes mostly respiratory illness, abortion or even subclinical infection, whereas piglets usually develop severe neurological signs.…”
Section: Introductionmentioning
confidence: 99%
“…In the performed infection assays, HEK293T cells were employed to investigate the effects of BAG3 overexpression or knockdown on lytic infection of PRV. We used HEK293T cells because: (i) Human cell lines are susceptible to PRV, and support the efficient replication of PRV [35,36], (ii) HEK293T cells are highly efficient for overexpression of foreign protein by the transfected plasmid, and (iii) PRV has been reported in several recent case reports to infect humans, which results in encephalitis [37][38][39][40][41][42]. Both overexpression and knockdown assays indicated that BAG3 played a negative regulation role during PRV lytic infection.…”
Section: Discussionmentioning
confidence: 99%
“…This patient got endophthalmitis 3 days after her eyes were exposed directly to the sewage of the farm (Ai et al, 2018). Another case was reported in 2019, in which the patient suffered from encephalitis and PRV gene fragments were detected in the cerebrospinal fluid and vitreous humor using next-generation sequencing (Wang et al, 2019), after which more cases of encephalitis resulting from PRV infection have been reported in China; most of the patients worked as farmers or veterinarians Yang X. et al, 2019;Fan et al, 2020;Li et al, 2020;Liu et al, 2020;Ou et al, 2020;Wang et al, 2020), suggesting that PRV infection in humans should not be neglected in the future (Wong et al, 2019).…”
Section: Introductionmentioning
confidence: 91%